Does prophylactic calcium in apheresis cause more harm than good? – Centre heterogeneity within the World Apheresis Association Register prevents firm conclusions. Issue 7 (6th August 2018) - Toss, Fredrik; Edgren, Gustaf; Berlin, Gösta; Stegmayr, Bernd; Witt, Volker
Abstract : Background and objectives: Symptomatic hypocalcaemia is common during apheresis procedures based on citrate‐based anticoagulants. As a consequence, patients often receive prophylactic calcium treatment. However, a recent publication based on the World Apheresis Association (WAA) register suggested harmful effects of such prophylactic calcium use. Recognizing possible limitations in the previous WAA register analyses, we critically re‐evaluate the data, to test whether a change in prophylactic calcium usage may be warranted. Materials and methods: Using the WAA register, we reanalysed previous data by means of centre and treatment type stratification, to explore the role of prophylactic calcium as a risk factor for adverse events. Results: There was large variability in adverse event rates dependent on the centre performing the apheresis procedure and dependent on the type of procedure. When this variability was accounted for, there was no clear effect of calcium administration on risk of adverse effects. Conclusion: Shortcomings in the previous WAA register analyses may have failed to account for important confounding factors resulting in a substantial overestimation of the risk attributable to calcium usage. Overall our findings do not support a negative effect of prophylactic calcium administration in the apheresis setting.